Liberdade de expressão em redes sociais: casos do jornalismo brasileiro - Christofoletti, Rogério (2012)
On enlarging the possibilities for interaction and participation of everyone in the production, distribution and consumption digital content on the web, social networks seem to contribute to give effect to and strengthen freedom of information and expression. However its use by journalists has revealed contradictions in the way how journalism is practiced/ conducted today. At the same time on that journalistic organizations seek to regulate the use of networks and social media can question the freedom of expression and communication of its professionals. The subject is controversial and lacks of examination. This article raises pertinent questions to the current conjuncture from the presentation of cases of journalists fired because of statements posted on their profiles on social networks. We reflect on freedom of expression, journalistic ethics and challenges of adaptation of journalists and companies. Analyze such problems implies not only adjust deontological codes and manuals, but, above all, rethink practices, norms and values that have been incorporated into the profession.